Where is 108? Possible under-utilization of the Copyright Act's library and archive-specific exemption from copyright infringement. Issue 4 (2nd October 2019) - Adams, Stephanie (Cole)
Abstract: This article addresses possible under-use of 17 U.S. Code §108 ("108"), the exemption to copyright infringement specifically for the protection of libraries and archives. This article was inspired by the personal experience of the author, a practicing attorney frequently advising libraries and archives, who has observed a lack of awareness and use of 108's significant protections. The article explores possible factors contributing to this lack of awareness, speculates on the impact of same, and proposes simple but critical actions that could increase and enhance library and archival operations' beneficial use of 108.